The oncologic impact of hormone replacement therapy in premenopausal breast cancer survivors: A systematic review. (August 2018) - Wang, Yimeng; Lewin, Naomi; Qaoud, Yazan; Rajaee, A. Nikoo; Scheer, Adena S.
Abstract: Synopsis: This is the first systematic review to investigate the risk of recurrence in breast cancer survivors <50 years old who have used hormone replacement therapy (HRT). Background: The risk of HRT in premenopausal breast cancer survivors is unclear. Due to the higher incidence of estrogen receptor negative tumours in women <50, the potential for HRT to promote breast cancer recurrence may differ from older age groups. Methods: We performed a search of Medline, EMBASE and CINAHL through June 2016. For the observational studies relative risk (RR) and 95% confidence interval (CI) were calculated for the recurrence rate among HRT users and nonusers. A random effects model was used to estimate the combined RR using the Mantel-Haenszel method. Results: Four papers satisfied our inclusion criteria. 3477 subjects were analyzed. On pooled meta-analysis of breast cancer recurrence in the observational studies, no significant association was found between HRT and risk of recurrence (RR 1.04 [95% CI 0.45, 2.41]). The randomized controlled trial (RCT) included found an increased risk of recurrence with HRT among women <50 (HR 1.56 [95% CI 1.1–2.2]). However, among women of all ages with an estrogen receptor negative tumour there was no significant difference in recurrence when compared to hormone receptor positive tumours (HR 1.15 [95% CI 0.7–1.8, p = 0.55]). Discussion: This review on HRT in breast cancer survivors <50 revealed conflicting results between randomized and observational study data. Further studies are warranted to investigate the association between HRT and recurrence rates in younger breast cancer survivors. Highlights: This review summarizes the best available evidence for hormone replacement therapy use in young breast cancer survivors. Hormone replacement therapy should be used with caution in young women with estrogen receptor positive breast cancer. In young women with triple negative breast cancers the data is limited but suggests a lack of harm.